Analisis Safety Maturity dengan Perspektif Change Management ADKAR di Bagian Operasional PT. ACB - Denny Dwi Ramadani; Tomi Oktavianor (JURNAL BISNIS DAN PEMBANGUNAN, 2025)
Abstract: The research method used is a qualitative approach, which allows the researcher to gain an in-depth understanding of the safety culture and the dynamics of change in the mining operational environment. Data collection techniques were conducted through in-depth interviews and document analysis. The key informants in this study were internal company sources, including the Operation Director, Head of Mining Engineering, and Technical Service Division Head. The research findings show that by using the ADKAR approach (Awareness, Desire, Knowledge, Ability, Reinforcement) in change management, PT ABC can improve their safety maturity level. Data analysis was conducted through theorybased thematic analysis, which helps maintain consistency between the theoretical framework of ADKAR and the data analysis performed. The study also provides practical recommendations that can be applied by the company to enhance their safety practices and change management. The research found that at PT ABC, safety awareness is high at the managerial level but not uniform across the organization, with the desire to change hindered by perceived workload. Safety knowledge exists, but implementation is weak, and reinforcement through rewards is inconsistent. The proposed strategies include raising awareness, providing incentives for change, practical training, intensive guidance, and continuous reinforcement